(untitled) (Historia, 2021)
Biographer Manning Marable argues that the "tendency of historical revisionism" posthumously interprets Malcolm X "through the powerful lens of Martin Luther King, Jr" and in doing so, is "unfair" to both. A similar dynamic can be observed within the South African context when Nelson Mandela is interpreted "through the powerful lens" of Albert Luthuli. The conflation is exacerbated when Luthuli is likewise "interpreted through the powerful lens" of Mandela; that for which each stood is inaccurately attributed to the other. Luthuli is wrongly portrayed as a supporter of armed revolution and Mandela is wrongly portrayed as an ideological descendant of Luthuli (of the same ilk as King and Mohandas Gandhi). King and Malcolm X differed on the tactical and moral utility of violence in the struggle for human rights as did Luthuli and Mandela. As political rivals, Malcolm X politically undermined King and Mandela politically undermined Luthuli. The author compares and contrasts King and Malcolm X’s respective views to develop themes related to the efficacy of pan-Africanism, violence and communism and identifies parallel themes in Luthuli and Mandela’s views. The recent revelation following Mandela’s death that he held membership in the South African Communist Party and served on its Central Committee during the early 1960s adds to the relevance of further examining how these icons are remembered and what role they played in South Africa’s liberation from oppression. Biograaf Manning Marable redeneer dat die "tendency of historical revisionism" Malcolm X postuum interpreteer "through the powerful lens of Martin Luther King, Jr" en is hierdeur onregverdig ("unfair") teenoor beide. ’n Soortgelyke dinamiek kan binne die Suid-Afrikaanse konteks waargeneem word wanneer Nelson Mandela "through the powerful lens" van Albert Luthuli geïnterpreteer word. Die samesmelting verskerp wanneer Luthuli eweneens "through the powerful lens" van Mandela geïnterpreteer word; dat dít waarvoor elkeen gestaan het, onjuis aan die ander toegeskryf word. Luthuli word verkeerdelik uitgebeeld as ’n ondersteuner van gewapende revolusie en Mandela word op sy beurt verkeerdelik voorgestel as ’n ideologiese afstammeling van Luthuli (van dieselfde klas as King en Mohandas Gandhi). King en Malcolm X het op die taktiese en morele geweldtoepassingsgebied in die stryd om menseregte verskil, soos ook Luthuli and Mandela. As politieke teenstanders is King polities deur Malcolm X ondermyn, en Luthuli eweneens deur Mandela. Die outeur vergelyk en kontrasteer King en Malcolm X se onderskeie sienswyses om temas te ontwikkel wat verband hou met die doeltreffendheid van pan-Afrikanisme, geweld en kommunisme en identifiseer parallelle temas in Luthuli en Mandela se sienswyses. Die onlangse openbaring na Mandela se dood dat hy oor lidmaatskap in die Suid-Afrikaanse Kommunistiese Party beskik het en in die vroeë sestigerjare in die twintigste eeu in die Sentrale Komitee daarvan gedien het, voeg toe tot die relevansie van verdere ondersoek na hoe hierdie ikone onthou word en watter rol hulle in Suid-Afrika se bevryding van onderdrukking vervul het.